SOCIOECONOMIC STATUS EFFECT ON MANAGEMENT OF HYPERTENSION IN COMMUNITY PHARMACY IN SOUTH- SOUTH ZONE IN NIGERIA - AA, Mgbahurike; SO, Oduogu; BM, Bagbi (Universal Journal of Pharmaceutical Research, 2021)
Background to study: Effective management of hypertension is influenced by several factors that center on social and economic status of the patient. Identification of these factors will enable informed intervention in the management of hypertensive patients. Objective: The study aimed to determine possible association between blood pressure control and socioeconomic status of patients who are managed in community pharmacies in Rivers State. Method: A descriptive cross-sectional survey of thirty-nine community pharmacies was conducted between July and December 2018. A total of 195 respondents participated in the study. Every patient’s consent was obtained. Further information on patients’ demographics were extracted from pharmacists’ documentation files. Such include age, medication patient is on, duration of hypertension, co-morbidity, income/ social status, and habits like smoking, alcohol consumption, educational status, and mean blood pressure over the study period. The outcome measure taken as controlled blood pressure was mean BP ≤140/90 mm Hg for the general population and BP 130/80 mmHg for patients with diabetes as co-morbidity. BP >140/90 mm Hg was considered as uncontrolled blood pressure. Result: A total of 195 respondents participated in the study, of which 105(53.8%) were male and 90(46.2%) were female. Out of this number 75(38.5%) were below 40yrs of age, 105(53.8%) were between 41–50yrs of age and only 15(7.7%) were 60yrs and above. More female had BP control compared to the male (OR 1.89, 95% CI (1.16 - 3.0), P=0.009. Patients within ages 41 - 59yrs had more controlled BP compared to older age, 60yrs and above, OR 1.48, 95% CI (0.84 - 2.42) p 0.18. Uncontrolled BP was found more among employed patients and patients with highest monthly income, OR 1.05 95% CI (0.58 - 2.00); OR 1.16 95% CI (0.49 - 2.78) P, 0.36 respectively. Exercise activities have significant impact on BP control as alcohol consumption increased OR of BP control with no significant difference in OR on amount of monthly expenditure on medications. Conclusion: Male gender, employment, and high income earning have negative effect on BP control while exercise is associated with BP control. Peer Review History: Received: 2 August 2021; Revised: 6 September; Accepted: 10 October; Available online: 15 November 2021 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Dr. Muhammad Zahid Iqbal, AIMST University, Malaysia, drmmziqbal@gmail.com Dr. Vanina Doris Edo’o, University of Yaounde I, Yaounde, Cameroun, vanina_edoo@yahoo.com